Wheat Proteins: A Valuable Resources to Improve Nutritional Value of Bread - Goel, Sonia; Singh, Mohinder; Grewal, Sapna; Razzaq, Ali; Wani, Shabir Hussain (Frontiers in Sustainable Food Systems, 2021)
Triticum aestivum is commonly known as bread wheat is one of the most cultivated crops globally. Due to its increasing demand wheat is the source of many nutritious products including bread, pasta, and noodles which contain different concentrations and kinds of seed storage proteins. In fact, the type and quality of any wheat product are largely controlled by these wheat proteins. Among various unique wheat products, bread is the most consumed product around the world due to its fast availability as compared to other traditional food commodities. The production of highly nutritious and superior quality bread is always a matter of concern because of its increasing industrial demand. Therefore, new and more advanced technologies are currently being applied to improve and enrich the bread having increase nutrients fortified, gluten-free, highly stable with enhancing shelf life, and long-lasting. In review, we focused on bread proteins in relation to improved the quality and nutritional properties of bread using modern technologies. We also describe the recent innovations in processing technologies to improve various quality traits of wheat bread. We also highlight some modern forms of bread that are utilizing in different industries for various purposes and propose future directions.